Vascular endothelial growth factor expression and angiogenesis in various grades and subtypes of meningioma - Priya Dharmalingam; V R Roopesh Kumar; Surendra Kumar Verma (Wolters Kluwer Medknow Publications, 2013)
Background: Vascular endothelial growth factor (VEGF) expression has been extensively studied in astrocytoma, whereas relatively less literature exists on VEGF expression in meningioma. Materials and Methods: Patients operated for meningioma from 2006 to 2011 (n = 46) were included. Tumor was subtyped and graded as per WHO grading. Immunohistochemistry was performed for MIB labeling index, VEGF, and CD 34 staining. The patterns of VEGF expression in various histological subtypes and grades and its correlation with microvascular density were analyzed. Results: This series consisted of 40 Grade I meningioma, 4 Grade II tumors, and 2 Grade III tumors. While 14 (30.4%) tumors showed no staining with VEGF antibody, 32 (69.6%) were positive for VEGF. Sixty five percent of Grade I tumors showed VEGF positivity, while 100% of Grade II and Grade III tumors were VEGF positive (P = 0.157). The mean microvascular density in VEGF-negative tumors was 9.00, while that of VEGF-positive tumors was 17.81(P = 0.013). There was a gradual increase in microvascular density from tumors which are negative for VEGF to tumors which expressed moderate to strong VEGF, the difference being statistically significant (P = 0.009). Conclusions: VEGF expression correlated with the microvascular density in meningioma irrespective of tumor grade, with a gradual increase in microvascular density in relation to the VEGF score.